Soil analysis for selected forage on-farm demonstration plots in Western Kenya - Nyawira, Sylvia Sarah; Jebet, Mercy Korir; Notenbaert, An Maria Omer (2022)
The data contains results for soil organic carbon and texture for selected forage treatments in 6 on-farm demonstration plots located in Bungoma, Kakamega, Siaya and Busia counties in Western Kenya. The soils were analyzed in 2022, 3 years after the planting of the forages. The 6 demonstration plots were set up within the Grass2cash project. The data will be used for calibrating and evaluating the DSSAT CROPGRO Perennial Forage Model.